Early diagenesis of organic-rich marls under shifting suboxic to euxinic conditions: The lower Toarcian of the Bächental basin. (October 2020) - Neumeister, Stefan; Misch, David; Algeo, Thomas J.; Gawlick, Hans-Jürgen; Gratzer, Reinhard; Sachsenhofer, Reinhard F.
Abstract: This study applied a multianalytical approach to identify active early diagenetic processes during deposition of the Lower Jurassic Bächental bituminous marls (Western Tethys realm). Results point to a major redox control on organic matter (OM) preservation and early diagenetic modifications. Whereas Mn reduction was the main OM oxidation process causing a maximum OM loss of ~1.5% and a lowering of hydrogen index values by up to 400 mgHC/gTOC under suboxic conditions, sulfate reduction was the dominant degradation process under anoxic-euxinic conditions. OM oxidation processes caused an increase of pH values (up to >9) and alkalinity in pore waters. These changes initiated carbonate precipitation in all samples, with high Mn-contents and predominant kutnohorite mineralization in suboxic layers, and presence of Mn-bearing calcite in anoxic units. The actual occurrence of the distinct carbonate phases (dolomite, kutnohorite, Mn-bearing calcite and siderite) reflects the redox pattern established by previous studies. Dissolution of biogenic silica and incipient alteration of pyrite in response to changing pore water pH and alkalinity conditions was found limited to the anoxic-euxinic intervals. In summary, this study provides detailed insights into the early diagenesis of organic-rich marls in a semi-restricted basin setting under varying oxygen depletion. Highlights: Early diagenetic processes in the Lower Jurassic Bächental bituminous marls identified. Mn reduction causing OM oxidation (OM loss of ~1.5 wt% in suboxic units). Lowering of hydrogen index values by up to 400 mgHC/gTOC under suboxic conditions. Early termination of sulfate reduction and enhanced OM preservation in anoxic-euxinic setting. Strongly redox-dependent formation of carbonate cements.